Ir–Cu nanoframes: one-pot synthesis and efficient electrocatalysts for oxygen evolution reaction. Issue 19 (11th February 2016) - Pei, Jiajing; Mao, Junjie; Liang, Xin; Chen, Chen; Peng, Qing; Wang, Dingsheng; Li, Yadong
Abstract : We achieved successful synthesis of alloy nanoframes, including bi-metallic and tri-metallic nanoframes, which show superior catalytic properties toward OER. Abstract : Herein, we achieved successful synthesis of uniform Ir–Cu nanoframes with highly open structures by a facile one-pot strategy. The key to obtain alloy nanoframes was the careful control over the reduction and galvanic replacement reactions between different metals. The as-prepared Ir–Cu was proved to be an effective template for constructing trimetallic nanoframes. Furthermore, these highly open nanostructures exhibited excellent electrocatalytic performance toward oxygen evolution reaction in alkaline media.